HUBUNGAN ANTARA KEYAKINAN DIRI DAN PERILAKU DISIPLIN BELAJAR DENGAN KEMANDIRIAN BELAJAR SISWA KELAS XI SMK SE-KABUPATEN BOJA - Harris Yuliawan; Eko Nusantoro (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2020)
This study aims to identify the relationship between Self Confidence and Discipline Learning Behavior with Learning Independence. This study uses a correlational design. Data were collected using self-confidence scale, learning discipline behavior questionnaire and learning independence scale of 289 students selected by cluster random sampling area technique. Hierarchical regression analysis results showed a positive prediction between self-confidence and learning discipline behavior with learning independence had a significant positive relationship (Î² = 0.622, Fcount = 181.313, t = 13.465, p = 0.00). This proves that the first hypothesis which reads "There is a significant positive relationship between Confidence with Learning Independence in students in SMKs in the Boja Region" can be accepted. The implications of the findings of this study are discussed in this article.Â